Verbal Mimesis: The Case of "Die Winzer." - Howard Stern (Studies in 20th & 21st Century Literature, 1983)
Paul Celan's "Die Winzer" (E. "The Vintagers") is a poem that narrates the story of its own composition and eventual reception through the metaphor of a ritual communion. At the same time, particularly in its rhythmic structure, the poem imitates that very communion by means of a traditional poetic device called "kinaesthesis" (in the recent semiotic terminology of W. K. Wimsatt). The essay is a reading of "Die Winzer" that develops its semiotic complexities and seeks to assign it a proper place in the general field of "verbal mimesis." The present author is not a philosopher, nor does he require a reader who is.
Keywords: Die Winzer; Paul Celan; The Vintagers; poem; narrates; composition; reception; metaphor; communion; ritual; kinaesthesis; W. K. Wimsatt; verbal mimesis